2015
DOI: 10.1161/strokeaha.115.010549
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Day Outcome of a Multicenter Registry Study of Stenting for Symptomatic Intracranial Artery Stenosis in China

Abstract: Background and Purpose-Although recent trials have suggested that stenting is worse than medical therapy for patients with severe symptomatic intracranial atherosclerotic stenosis, it is not clear whether this conclusion applies to a subset of patients with hypoperfusion symptoms. To justify for a new trial in China, we performed a multicenter prospective registry study to evaluate the safety and efficacy of endovascular stenting within 30 days for patients with severe symptomatic intracranial atherosclerotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
88
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 26 publications
7
88
3
Order By: Relevance
“…Tailored endovascular treatment of using balloon-mounted stent or balloon plus self-expanding stent for ICAD was based on anatomical features and lesion morphology. The 30-day rate of stroke, TIA, and death was 4.3% (13/300) [22]. Gao et al enrolled patients with recent TIA or ischemic stroke related to high-grade stenosis of a major intracranial artery and with distal hypoperfusion and/or cortical involvement but excluded patients who had ischemic symptoms within the recent 3 weeks and perforator ischemic events.…”
Section: Discussionmentioning
confidence: 99%
“…Tailored endovascular treatment of using balloon-mounted stent or balloon plus self-expanding stent for ICAD was based on anatomical features and lesion morphology. The 30-day rate of stroke, TIA, and death was 4.3% (13/300) [22]. Gao et al enrolled patients with recent TIA or ischemic stroke related to high-grade stenosis of a major intracranial artery and with distal hypoperfusion and/or cortical involvement but excluded patients who had ischemic symptoms within the recent 3 weeks and perforator ischemic events.…”
Section: Discussionmentioning
confidence: 99%
“…The VISSIT trial did not support the use of BES (Zaidat et al 2015). Nevertheless, Miao revealed the safety and efficacy of endovascular stenting (Miao et al 2015). The reporters found that there was no significant difference between the SES and the BES about the follow-up clinical outcomes (Yue et al 2011b).…”
Section: Discussionmentioning
confidence: 99%
“…The problem was resolved by the BES. BES may have a lower degree of residual stenosis than SES (Miao et al 2015). We obtained an outstanding angiographic result with BES.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 16 The first one was a single-centre randomised trial, the results of which demonstrated that PTAS is as effective as medical treatment 16. The result of the second study, a multicentre registry study, showed that the incidence of stroke, transient ischaemic attack (TIA) and death in 30 days after stenting was 4.3%, which is lower than the incidence in the SAMMPRIS trial 17. The third study was a retrospective study.…”
Section: Introductionmentioning
confidence: 99%